Comparison of quality of sausages from chicken and rabbit meat - KUMAR, SUSHIL; MENDIRATTA, S K; KESHRI, R C (The Indian Journal of Animal Sciences, 2013)
Studies were, conducted to compare quality parameters of sausages prepared from chicken and rabbit meat in proportions of 100:0, 75:25, 50:50, 25:75 and 0:100 respectively. Results indicated significantly (P